2018
DOI: 10.1080/02640414.2018.1473993
|View full text |Cite
|
Sign up to set email alerts
|

The influence of` preseason training phase and training load on body composition and its relationship with physical qualities in professional junior rugby league players

Abstract: This study investigated changes in body composition in relation to training load determined using RPE and duration (sRPE), and its relationship with physical qualities over a preseason period. Sixteen professional academy players (age = 17.2 ± 0.7 years; stature = 179.9 ± 4.9 cm; body mass = 88.5 ± 10.1 kg) participated in the study. Body composition was assessed before and after each training phase and physical qualities assessed at the start and end of preseason. Across the whole preseason period, skinfold t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 30 publications
2
25
2
Order By: Relevance
“…During pre-season, players are physically overloaded in order to facilitate a super-compensatory response, and in turn, improve physical capabilities. 54 The total number of pre-season training sessions documented in the current study are greater than previously reported in academy rugby league, Dobbin et al 10 reported 37 total pre-season training sessions, which is lower than our results (106). However, the aforementioned study only included resistance, conditioning and rugby sessions.…”
Section: Training Practicescontrasting
confidence: 84%
See 2 more Smart Citations
“…During pre-season, players are physically overloaded in order to facilitate a super-compensatory response, and in turn, improve physical capabilities. 54 The total number of pre-season training sessions documented in the current study are greater than previously reported in academy rugby league, Dobbin et al 10 reported 37 total pre-season training sessions, which is lower than our results (106). However, the aforementioned study only included resistance, conditioning and rugby sessions.…”
Section: Training Practicescontrasting
confidence: 84%
“…1,5 To date, extensive research has investigated the characteristics of rugby league match play, 4,6,7 and the physical qualities of players across different age categories and playing standards. [8][9][10] In order to develop rugby league players for elite competition, understanding the performance and development of physical qualities is essential. There are several studies available that describe the physical qualities of rugby league players, 1,9,[11][12][13] and their associations with match performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 These characteristics are essential for players to succeed 1 and should be central to rugby league conditioning practices. 2 Developing the physical characteristics of rugby league players is the focus of preseason; 3,4 thereafter emphasis is placed on recovery, technical and tactical development, and match preparations. 5 This change in focus and reduced exposure to maximal-intensity work during training might explain the observed reductions in physical characteristics such as high-intensity intermittent running ability, sprint speed and lower-body power during the latter stages of a ~28-week season.…”
Section: Introductionmentioning
confidence: 99%
“…Attention should also be paid to chemical and tissue composition and components in the somatotype. Undoubtedly, the shape and form of the body are most importantly influenced by its two main so-called plasticisers, muscular and fat tissue, and the third fundamental factor -the skeletal system [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%